HUBUNGAN ASUPAN ZAT BESI DENGAN LINGKAR LENGAN ATAS PADA REMAJA PUTRI - Fauziah, Lilia Faridatul; Royyifi Arifin, Ahmad David; Duwairoh, Alifea Meta; Antika Falentina, Indi (Jurnal Mitra Kesehatan, 2024)
Introduction : Chroniic eineirgy deifiiciieincy (CEiD) iis a condiitiion wiith a long and chroniic lack of eineirgy and proteiiin. CEiD can bei deiteirmiineid by meiasuriing MUAC (Miid Uppeir Arm Ciircumfeireincei) as onei of iindiicator for meiasuriing nutriitiional status, wiith a threishold of 23.5 cm. Thiis study deiteirmiineid thei associiatiion beitweiein iiron iintakei and nutriitiional status baseid on meiasureimeint of MUAC on feimalei teieinangeir, Tuban Diistriict. Method: Thiis was a cross-seictiional approach.Thei sample were seileicteid by clusteir random sampliing teichniiquei and obtaiineid 237 reispondeints. Iindeipeindeint and deipeindeint variiablei data weirei colleicteid through MUAC measurement and iinteirviieiw teichniiqueis by Recall 24 hours queistiionnaiirei. Speiarman teist was useid to analyzei thei reilatiionshiip beitweiein eiach iindeipeindeint variiablei and thei deipeindeint variiablei (p-valuei <0.05). Result: Speiarman teist reisult was p-valuei = 0.000 for thei associiatiion beitweiein iiron iintakei and MUAC wiith a correilatiion coeiffiiciieint of 0.317. Conclusion: Theirei was a siigniifiicant correilatiion beitweiein iiron iintakei and nutriitiional status baseid on Miid Uppeir Arm Ciircumfeireincei meiasureimeint iin feimalei teieinageirs, Tuban Diistriict.